Redefining Dispersal Boundaries of Siganus fuscescens In The Coral Triangle Area - Ni Putu Dian Pertiwi; Nur Ismu Hidayat; Chloe Henderson; I Nyoman Giri Putra; Andrianus Sembiring (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
The increasing demand of fish in the Coral Triangle Area has led to overexploitation of some species of fishes. One of the commercial fishes, which is also known to be the source of food and income for local communities, is the Mottled Spinefoot (Siganus fuscescens). Population studies on this species are important in order to manage sustainable stock populations. Genetic variation of the mitochondrial DNA was analyzed to examine the population structure of Siganus fuscescens in Indonesia, as part of the Coral Triangle Area. In total, 789 basepairs of control region mtDNA sequences were determined from 133 specimens collected from six localities, including Seribu Islands (n=27), Karimunjawa (n=19), Komodo (n=39), Selayar (n=20), Lembeh (n=19) and Luwuk (n=9). From the data, 27 variable sites and 24 haplotypes were detected, with most of the haplotypes unique to each location. Haplotype data show that one haplotype was shared among all populations, three haplotypes were shared between two populations (Komodo & Selayar; Lembeh & Seribu; Komodo & Karimunjawa), and 20 were unique to a single population. Haplotype diversity (h=0.444) and nucleotide diversity (π=0.00165) were low. The diversity result, i.e. the ΦST value (0.0658, P < 0.0001) revealed genetic structure in S. fuscescens populations in Indonesia. A non-dispersal strategy led to restricted gene flow and genetic structuring in S. fuscescens. However, both the neutrality test and the mismatch distribution indicated that S. fuscescens might have been in populations at demographic equilibrium, with restriction to the population expansion. Although indicating unexpected minor population structure pattern, the overall result still suggest the management of this species population as a single unit across Indonesia.